Parallelism-Aware Batch Scheduling: Enabling High-Performance and Fair Memory Controllers - Mutlu, Onur; Moscibroda, Thomas (MICRO TOP PICKS 2009: IEEE Micro. Special Issue: Micro's Top Picks from 2008 Computer Architecture Conference, 2009)
Uncontrolled interthread interference in main memory can destroy individual threads’ memory-level parallelism, effectively serializing the memory requests of a thread whose latencies would otherwise have largely overlapped, thereby reducing single-thread performance. PAR-BS, the parallelism-aware batch scheduler, preserves each thread’s memory-level parallelism, ensures fairness and starvation freedom, and supports system-level thread priorities.